Low Temperature Sintering of Aluminum-Zircon Metal Matrix Composite Prepared by Spark Plasma Sintering - Ehsan Ghasali; Hossein Nouranian; Ali Rahbari; Houdsa Majidian; Masoud Alizadeh; Touradj Ebadzadeh (Materials Research, 2016)
Aluminum-15 wt. % zircon metal matrix composite was fabricated using spark plasma sintering method at the temperature of 450°C and holding time of 4 min. The bending strength of 284±21 MPa and microhardness of 171±14 Vickers were determined for produced composite. XRD investigations proved that almost no decomposition of zircon particles as reinforcement occurred. SEM studies revealed the homogenous dispersion of reinforcement particles in the aluminum matrix.